Effect of Ketotifen and Cyproheptadine on Appetite and Weight Changes in Mice: Change of appetite and weight by antihistamins - Nemati, Mahboob; Habibi Asl, Bohlool; Sharifi, Kamran (Iranian Journal of Pharmaceutical Sciences, 2006)
Ketotifen is a potent, safe and long acting antihistamine that is effective in treatment of asthma and its use is believed to causes weight gain and drowsiness. Cyproheptadine, an antihistamine, has anticholinergic and antiserotonergic effects, and causes increases of the appetite and weight gain. In this study the effects of different doses of ketotifen and/or cyproheptadine on the appetite and weight changes in mice is evaluated. Sixty four male mice were divided in 8 groups and received the following drug regimens for 45 days. Control group, normal saline (10 ml/kg, s.c.), three groups of cyproheptadine (5, 10, 20 mg/kg, s.c.), three groups of ketotifen (8, 16, 32 mg/kg, s.c.), and one group cyproheptadine (5 mg/kg, s.c.) combined with ketotifen (8 mg/kg, s.c.). Weight changes caused by above drug regimens were recorded every 2 days and average of food intake was recorded every day for 45 days. The results showed that the high dose of ketotifen (32 mg/kg, s.c.) increased weight, significantly, but its low dose (8 mg/kg, s.c.) decreased weight significantly. Cyproheptadine (5 mg/kg, s.c.) caused significant increase in weight gain and stimulated appetite, but its high dose of (20 mg/kg, s.c.), decreased the appetite and weight. Co-administration of cyproheptadine and ketotifen decreased the appetite, significantly. The results showed that different doses of cyproheptadine and ketotifen have different effects on the appetite and weight gain in mice, and possibly different mechanisms of action.